2009
DOI: 10.1063/1.3067855
|View full text |Cite
|
Sign up to set email alerts
|

Influence of annealing and phase decomposition on the magnetostructural transitions in Ni50Mn39Sn11

Abstract: Magnetic and structural transitions in the Ni 50 Mn 50−x Sn x (x = 10-25) ferromagnetic shape memory alloys are currently of interest. As in Ni-Mn-Ga, these alloys feature high-temperature austenite and lowtemperature martensite phases, where the magnetic state is strongly composition dependent. To study the role of chemical ordering in fine-tuning their magnetostructural properties, they were first annealed for 4 weeks/ 1223 K to achieve structural and compositional homogeneity, and were then further annealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 14 publications
5
27
0
2
Order By: Relevance
“…4) features a eutectoid-like microstructure. These regions did not display any structural transformation between 109 and 443 K-consistent with the type of behavior observed in Ni 50 Mn 39 Sn 11 eutectoid structures [27].…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…4) features a eutectoid-like microstructure. These regions did not display any structural transformation between 109 and 443 K-consistent with the type of behavior observed in Ni 50 Mn 39 Sn 11 eutectoid structures [27].…”
Section: Resultssupporting
confidence: 56%
“…Phase decomposition into two phases was confirmed by TEM analysis of Ni 50 Mn 39 Sn 11 , following the 1-week anneal at 773 K [27]. Detailed analysis of the TEM micrograph (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The chemical formulas are Ni 50.1 Mn 30.5 Sn 17.3 Co 2.1 and Ni 59 Mn 32.5 Sn 2.5 Co 6 , respectively. It is in good agreement with the reported decomposition of Ni 50 Mn 50−x Sn x into Ni 50 Mn 30 Sn 20 and Ni 54 Mn 45 Sn after 4 weeks annealing at 1223 K (Yuhasz et al, 2009). As the chemical composition of Ni 59 Mn 32.5 Sn 2.5 Co 6 is closer to that of NiMn, the alloy should be crystallized in the NiMn-type structure and Ni 50.1 Mn 30.5 Sn 17.3 Co 2.1 as the L2 1 austenite phase.…”
Section: Resultssupporting
confidence: 93%
“…Annealing times of 1 h or 2 h did not suffice to dissolve the netlike segregations, but in contrast an annealing time of 72 h did. Also Yuhasz et al showed that an extended annealing (about 4 weeks) at 1223 K is needed to gain a chemical and structural homogenization for Ni 50 Mn 50−x Sn x (x = 11-15) [14].…”
Section: Introductionmentioning
confidence: 99%